Contests for Meaning: Ableist Rhetoric in Video Games Backlash Culture - Hayley R. Crooks; Shoshana Magnet (Disability Studies Quarterly, 2018)
An increasing number of video games focus on empathetic identification across difference. Since the mid-2000s, games that encourage catharsis and immersive engagement with trauma range from the personal as in That Dragon, Cancer (2014), in which players experience what it is like to parent a terminally ill child to geopolitical struggles as in Peacemaker (2007) which encourages player empathy for both sides of the Israeli-Palestinian Conflict. These games are rapidly gaining in popularity and commercial backing. As more games focus on issues of social justice, the backlash against these concerns among a vocal segment of the gaming community is increasing in frequency and intensity. A branch of the men's rights movement has focused on video games aimed at understanding difference, and has attracted attention suggesting that all those advocating for social justice in games (dubbed Social Justice Warriors) should be understood to have narcissistic personality disorder (NPD). We argue that these claims to NPD need to be understood as a form of structural ableism mobilized by the men's rights movement. In doing so, we argue that by situating the mental health labels evoked by current men's rights' activist rhetoric about feminist anti-racist interventions in game culture is a new form of the old practice of attaching mental health labels to people challenging social norms underpinning the dominant culture.
Keywords: Gamer Culture; Ableism; Racism; Video Games; Misogyny; Feminist Game Studies